Adoption Spells of Improved Potato Varieties by Smallholder Farmers in Eastern Ethiopia: The Duration Approach - Sisay Lemessa; Molla Alemayehu; Megersa Daksa; Nigussie Dechassa (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
Potato is mainly tagged as a food security crop in Ethiopia. However, its productivity remains low due to low adoption of improved technologies by smallholder farmers. Duration models, namely, Parametric (Weibull) and Non-parametric (Kaplan Meier) were used to analyze the data gathered from 365 sample farmers. The Non-parametric result revealed that the average duration that potato growers should wait before adopting a new variety is about 3.5 years. The Weibull regression indicated that timely availability of seed, access to labor and irrigation water, land size, and adaptation strategy by farmers are found to be factors curtailing the timeframe to adopt improved potato varieties. The regression analysis revealed that costs of inputs such as manure and compost, environmental and market factors such as drought, pest and disease outbreaks, price variability of potato seed, and quality of potato seed were found to be factors influencing adoption decisions of improved potato varieties by smallholder farmers.